The effect of time constraints and running phases on combined event pistol shooting performance. Issue 11 (2nd June 2016) - Dadswell, Clare; Payton, Carl; Holmes, Paul; Burden, Adrian
ABSTRACT: The combined event is a crucial aspect of the modern pentathlon competition, but little is known about how shooting performance changes through the event. This study aimed to identify (i) how performance-related variables changed within each shooting series and (ii) how performance-related variables changed between each shooting series. Seventeen modern pentathletes completed combined event trials. An optoelectronic shooting system recorded score and pistol movement, and force platforms recorded centre of pressure movement 1 s prior to every shot. Heart rate and blood lactate values were recorded throughout the event. Whilst heart rate and blood lactate significantly increased between series ( P < 0.05), there were no accompanying changes in the time period that participants spent aiming at the target, shot score, pistol movement or centre of pressure movement ( P > 0.05). Thus, combined event shooting performance following each running phase appears similar to shooting performance following only 20 m of running. This finding has potential implications for the way in which modern pentathletes train for combined event shooting, and highlights the need for modern pentathletes to establish new methods with which to enhance shooting accuracy.